High-Quality S&T Human Resources Social Mobility in Vietnamese Universities: The Case of Vietnam National University, Hanoi and Vietnam National University, Ho Chi Minh City - Dang, Kim Khanh Ly (H. : ĐHQGHN, 2019)
In the context of all countries striving towards a dynamic and developedeconomy, labour resources have a direct effect on the growth of any economy. Obviously, as labour resources are a highly influential factor for economic development, quality labour resources will facilitate the development and without them, it will be hindered. In respect of this, the social mobility of labour resources, especially high-quality S&T human resources, has become an issue of major concern to organizations and countries. Although there are many types of the social mobility, this article focuses on only two major types: 1) social mobility with migration, also known as "brain drain" and 2) social mobility without migration – "internal brain drain". The research data shows the current status of the social mobility of high-quality S&T human resources within two Vietnam national universities: Vietnam National University, Hanoi and Vietnam National University, Ho Chi Minh City, for defining the mobility’s trends. The article concludes with a number of suggestions for relevant policy planning to minimize the negativeimpacts of the social mobility and to improve the efficiency of using high-quality S&T human resources in Vietnamese universities.